SPECIFIC ASPECTS OF STRATEGIC MANAGEMENT IN THE HIGHER EDUCATION SYSTEM AND ISSUES OF THEIR IMPROVEMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Uzbekistan supreme education in the system strategic management mechanism education environment develop and his/her quality indicators in increasing important factor as manifestation This is happening . in the article strategic management system main directions , features and his/her practical results scientific in terms of analysis In particular , our country supreme education in institutions strategic management important signs as to the goal orientation , flexibility , systematicity , quality management and far term planning such as factors separate is displayed . Strategic management effective current to grow as a result education of quality increase , international cooperation of relations expansion , development production , innovation and technologies with integration increase , academic mobility development , as well as stable development and social responsibility level increase is being observed . Modern under the circumstances strategic management system improvement through supreme education in the system quality indicators improvement , international integration expand , develop release with integral dependency provide and competitive experts to prepare This process is being achieved . of the country stable development in providing important importance profession will reach .
Keywords: flexibility , science and education integration , quality management , education programs , graduates employment , academic mobility , social responsibility .